2022
DOI: 10.3389/fevo.2022.1063736
|View full text |Cite
|
Sign up to set email alerts
|

Does ESG performance promote total factor productivity? Evidence from China

Abstract: Currently, environmental, social, and corporate governance (ESG) has become an all-pervasive term in the industrial sector, owing to its significant impact on corporate decision-making. While most of the studies provide evidence that the ESG significantly improves a firm's performance and value in the long run, few studies quantitatively analyzed the linkage between ESG and total factor productivity (TFP). Using the data of Chinese-listed companies during 2010–2020, we found that there is a positive relationsh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…To test the relationship between ESG performance and stock liquidity, we followed Ma et al (2022) to construct the following baseline regression model:…”
Section: Methodsmentioning
confidence: 99%
“…To test the relationship between ESG performance and stock liquidity, we followed Ma et al (2022) to construct the following baseline regression model:…”
Section: Methodsmentioning
confidence: 99%
“…To test hypothesis H1: enterprises can improve total factor productivity by practicing the ESG concept, enhancing their long-term value, and realizing a win-win of social value and commercial value. Based on the theoretical models of Xu and Zhao [ 26 ], Ma, Gao [ 30 ], this paper constructs the following model to reflect the impact of ESG on TFP: …”
Section: Variables Models and Datamentioning
confidence: 99%
“…However, there is a significant positive correlation between ESG performance and total asset turnover (TAT) and equity multiplier (A/E) [54]. Ma and Sun found that firms with high ESG performance can increase total factor productivity by alleviating financing constraints and enhancing innovation levels [16]. Velte P found that ESG performance is negatively related to accrual-based surplus management but does not affect actual surplus management in a sample of German firms.…”
Section: Esg Performancementioning
confidence: 99%
“…Ali et al, Lorenzo et al, and Fan et al argue that the development of information technology has significantly increased tax authorities' ability to collect taxes, inhibiting corporate tax avoidance and increasing their tax burden [11][12][13]. In the existing literature on ESG performance, scholars have mainly focused on the impact of ESG performance on financial performance [14], corporate value [15], financing constraints, and other aspects of economic consequences [16] and less on the factors influencing ESG performance.…”
Section: Introductionmentioning
confidence: 99%